Psychopathological disorders in adolescents of the Republic of Tuva with different types of online behavior - Evert, Lidiya S. (The New Research of Tuva, 2026)
The article analyzes problems of psychopathological spectrum disorders in adolescents and young people in the Republic of Tuva with different types of online behavior: adaptive, maladaptive, and pathological. The analysis is based on the results of online testing of random samples of individuals of adolescent and youth age, conducted in 2022–2023 (1,028 participants: 76 Russians and 952 Tuvans) using Google Forms, a screening questionnaire, and psychometric scales to verify the type of online behavior and components of Internet content. To assess psychopathological disorders in the study participants, the Symptom Checklist SCL-90-R was used, which makes it possible to verify the characteristics of nine scales. The analysis included indicators of six of them: obsessiveness–compulsiveness, interpersonal sensitivity, hostility, phobic anxiety, paranoid ideation, and psychoticism, as well as integral indices: intensity of distress and the global severity index of symptoms. It was found that, regardless of the type of online behavior, the Tuvan part of the sample is characterized by a lower level of distress intensity (47.9% among Tuvans and 34.9% among Russians). Ethnic differences were identified in groups with the same type of online behavior. Among both Russians and Tuvans with pathological Internet use, pronounced obsessiveness–compulsiveness, interpersonal sensitivity, hostility, paranoid ideation, psychoticism, as well as increased intensity of distress and a high global severity index of symptoms were recorded significantly more often. Among respondents with adaptive online behavior, a larger proportion of individuals with a high level of obsessiveness–compulsiveness and a high global severity index of symptoms was observed in the Russian group compared to their Tuvan peers. Tuvan adolescents with adaptive and maladaptive types of online behavior were more often characterized by low distress intensity than comparable groups of representatives of the Russian ethnic group.